2006
DOI: 10.1590/s0066-782x2006001800006
|View full text |Cite
|
Sign up to set email alerts
|

Dez anos de experiência com a operação de Ross

Abstract: Late outcomes with the Ross Operation were associated with an excellent long-term survival and a low incidence of reoperations and late morbidity. We consider this procedure the best option for the surgical treatment of aortic valve disease in children and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…de Cushing e o feocromocitoma e assim como no DM, a excreção da glicose na urina é presente pois o limiar renal da glicose é excedido 10, 11,12 .…”
Section: Discussionunclassified
“…de Cushing e o feocromocitoma e assim como no DM, a excreção da glicose na urina é presente pois o limiar renal da glicose é excedido 10, 11,12 .…”
Section: Discussionunclassified
“…Over the ten years of this study, aortic valve homografts were not considered the first choice for replacement for only under 50-year-old patients (in these cases the Ross operation was preferred), in patients who required simultaneous implantation of a conventional valve prosthesis in the mitral valve position, when no adequate homograft was available during the surgery or if patients chose a mechanical valve prosthesis [10].…”
Section: Discussionmentioning
confidence: 99%
“…By an extremely careful evaluation, using maximum instantaneous gradients of over 40 mmHg or moderate valve insufficiency to identify cases of dysfunction, we observed that only 44% of the under 20-year-old patients presented with normal functioning homografts after ten years of follow up. For this reason, in under 40-year-old patients, we perform the Ross operation [1,10], reserving the use of homografts only for cases when the use of pulmonary autograft is not possible or in severe rheumatic mitralaortic patients, in which the damage of the mitral valve is extensive and with a more limited long-term prognosis. On the other hand, in over 40-year-old patients, the probability of homograft valve dysfunction is less than 5%.…”
Section: Discussionmentioning
confidence: 99%